Behavior of composite slab consisting of foam concrete and normal concrete - Lim, Gee Zhiong (Universiti Malaysia Sarawak (UNIMAS), 2009)
In this new era, many mega structures have been built all around the world. Day by day human being keep on improving the structures that have been never thought that it will be possible to build in the past. Many mega structures are using lightweight concrete to fulfils some of the requirements during designing stage. However, due to some limitations; lightweight concrete do not have high strength in terms of compression or tension. Normal concrete has high compressive strength but it is not lightweight which contribute loading to the structure itself. The idea of combination of normal concrete and foam concrete is to produce a lightweight but strong structure. This study discusses the investigations done to behavior of composite consisting of normal concrete and foam concrete by identifying few parameters and the influence of these parameters on density and strength. The results were observed and studied for further analysis. It is found that the composite concrete consisting of normal and foam concrete is still able to perform well under the applied loading. The flexural and compressive strength of foam concrete can be improved by combining with normal concrete. Normal concrete can be called lightweight concrete while maintaining its high strength.